(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2025)
Trigona honey is a stingless bee product rich in secondary metabolites and recognized for its antioxidant properties. Pineapple also contains bioactive phytochemicals. Therefore, their combination through fermentation has the potential to produce a functional product. This study aimed to evaluate the phytochemical profile and antioxidant activity of Trigona honey fermented with pineapple for seven days. The honey originated from nectar nutmeg (Myristica fragrans), mangosteen (Garcinia mangostana), and durian (Durio zibethinus). Analyses included pH, moisture, alcohol content, sugar profile, total phenolics, saponins, and antioxidant activity. Fermentation decreased pH due to microbial acid production and increased moisture. Glucose and sucrose declined from 6.13% and 4.83% on day 4 to 3.99% and 1.47% on day 7, respectively. Alcohol content rose to 6.21% w/w, indicating active Saccharomyces cerevisiae metabolism. Total phenolic content decreased from 1.508 to 0.541 mg TAE/g on day 4 and rose slightly to 0.707 mg TAE/g on day 7. Saponin content dropped from 573.16 to 147.66 mg KOH/g on day 4, increasing to 429.84 mg KOH/g on day 7. Antioxidant activity rose significantly from 3.17% to 24.36%. These results show that seven day fermentation enhances antioxidant activity while modifying honey’s phytochemical properties, making it a potential functional product from tropical Indonesia.